A comparative study of the bispecific monoclonal antibody, blinatumomab expression in CHO cells and E. coli. Issue 10 (26th November 2018) - Naddafi, Fatemeh; Shirazi, Farshad H.; Talebkhan, Yeganeh; Tabarzad, Maryam; Barkhordari, Farzaneh; Aliabadi Farahani, Zahra; Bayat, Elham; Moazzami, Reza; Mahboudi, Fereidoun; Davami, Fatemeh
Abstract: The "bispecifics" market improved over the past decade due to the development of many technological platforms including bispecific T cell engagers (BiTEs). The approval of blinatumomab, the most advanced bispecific T-cell engager (BiTE) in clinical trials, can be a significant milestone in the development of bispecific antibodies. Both Chinese hamster ovary (CHO) cells and E. coli strain are considered as the most widely used hosts for the large-scale production of therapeutic monoclonal antibodies. Since both of the economic and qualitative aspects of protein production are important in industry, selection of a suitable protein expression system is very critical. The BsAb gene was cloned into the expression vectors FC550A-1, pcDNA3.1 (+), and PET22b and 6 × His-tagged BsAb then purified on a Ni-NTA chromatography column. Both SDS–PAGE and Western blotting analysis of the purified protein demonstrated that blinatumomab was successfully expressed as a 55 kDa in both expression systems. The antigen-binding properties of blinatumomab were compared in the mammalian system versus Escherichia coli . The results showed that the purified antibody from a mammalian expression system has better binding activity than the one from E. coli host.